Ocena konkurencyjności polskiego przemysłu spożywczego w Unii Europejskiej - Szczepaniak, Iwona (An Assessment of Competitiveness of Polish Food Industry in the European Union, 2006)
An assessment of competitiveness of Polish food producers is based in the paper upon an analysis of two ratios, i.e.: 1) value of exports to the EU, imports from the EU and balance versus the value of domestic sales in main branches of food industry; 2) domestic prices of chosen agriculture products versus relevant prices in the EU; 3) domestic prices at factory gate versus relevant prices in Germany. The performance of Polish food industry in the first months after the accession confirmed reasonable scope of preparations to operate on the common market. Polish food producers skilfully benefited from comparative advantages mainly resulting from lower prices. It was mirrored in growing agrifood exports, improvement of the balance of trade and strengthening position of Polish producers in the enlarged EU. The accession of Poland to the EU structures did not result in an excessive inflow of imported food products from the EU. The increase of export of Polish food industry was common place. However, there were large differences among the branches. In the medium run Polish food industry has tangible opportunities to increase its competitiveness. As our comparative advantage resulting from price differential will be reduced and the competition of EU food producers will increase the situation of Polish food industry in the long run is going to be more difficult.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 384-391